Highly selective custom‐made chitosan based membranes with reduced fuel permeability for direct methanol fuel cells. Issue 46 (9th July 2021) - Divya, Kumar; Rana, Dipak; Rameesha, Laila; Sri Abirami Saraswathi, Meenakshi Sundram; Nagendran, Alagumalai
Abstract: Custom‐made nanocomposite proton exchange membranes (PEMs) are fabricated using the blends of sulfonated chitosan (S‐Chitosan) and sulfonated graphene oxide (SGO) nanosheets for direct methanol fuel cells (DMFCs). Sulfonation of chitosan and GO are carried out by 1, 3‐propane sultone and sulfanilic acid, respectively. Scanning electron microscope (SEM) with energy dispersive X‐ray investigation revealed that the thick, folded and wrinkled sheet‐like morphology of SGO and the existence of elemental sulfur. SEM and atomic force microscopy images showed the uniform dispersion of hydrophilic SGO nanosheets. Besides the S‐Chitosan/SGO membranes showed higher water uptake, swelling ratio and ion exchange capacity due to the enhancement in hydrophilicity. The modified PEMs displayed improvement in proton conductivity since the ion‐exchangeable sulfonic acid groups facilitate the proton conduction and effectively resist the methanol permeability by forming a strong hydrogen bond network with chitosan and thus diminish the void volume. Particularly, S‐Chiotsan‐1 membrane showed superior proton conductivity of 4.86 × 10 −3  Scm −1 at (25°C), selectivity of 1.89 × 10 5  Scm −3 s and lesser methanol permeability of 2.57 × 10 −8  cm 2 s −1 . Overall results suggest that the S‐Chitosan/SGO membranes found to be a suitable alternate for Nafion® in DMFCs. Abstract :